2021
DOI: 10.1111/sms.13976
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, fatness, and the acute blood pressure response to exercise in adolescence

Abstract: Objective Exaggerated exercise blood pressure (BP) is associated with cardiovascular risk factors in adolescence. Cardiorespiratory fitness and adiposity (fatness) are independent contributors to cardiovascular risk, but their interrelated associations with exercise BP are unknown. This study aimed to determine the relationships between fitness, fatness, and the acute BP response to exercise in a large birth cohort of adolescents. Methods 2292 adolescents from the Avon Longitudinal Study of Parents and Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In this study, exercise BP also had a stronger positive association with elevated body fatness compared to the independent negative relationship with PWC 170 . These findings are consistent with other cross‐sectional studies where exercise systolic BP was higher among individuals with elevated body fatness irrespective of cardiorespiratory fitness 25,26 . A decrease in exercise BP has also been found to be independently associated with a reduction in waist circumference and improvement in cardiorespiratory fitness following an exercise intervention 27 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, exercise BP also had a stronger positive association with elevated body fatness compared to the independent negative relationship with PWC 170 . These findings are consistent with other cross‐sectional studies where exercise systolic BP was higher among individuals with elevated body fatness irrespective of cardiorespiratory fitness 25,26 . A decrease in exercise BP has also been found to be independently associated with a reduction in waist circumference and improvement in cardiorespiratory fitness following an exercise intervention 27 .…”
Section: Discussionsupporting
confidence: 90%
“…These findings are consistent with other cross-sectional studies where exercise systolic BP was higher among individuals with elevated body fatness irrespective of cardiorespiratory fitness. 25,26 A decrease in exercise BP has also been found to be independently associated with a reduction in waist circumference and improvement in cardiorespiratory fitness following an exercise intervention. 27 The current study also expands on this understanding between exercise BP, body fatness, and PWC 170 and shows these relationships were partly mediated via relations with general CVD risk factors, suggesting other contributory factors may also influence the BP response.…”
Section: Discussionmentioning
confidence: 99%
“…However, females with obesity also exhibited augmented BP responses during handgrip exercise, indicating heightened time–averaged sympathetic vascular transduction 179 . Similarly, others have reported augmented BP responses during exercise in individuals with obesity 189–192 . Studies in participants with obesity who underwent weight loss through diet and/or exercise also exhibit attenuated MSNA during stressors.…”
Section: Autonomic Nervous System Control Of Blood Pressurementioning
confidence: 96%
“…179 Similarly, others have reported augmented BP responses during exercise in individuals with obesity. [189][190][191][192] Studies in participants with obesity who underwent weight loss through diet and/or exercise also exhibit attenuated MSNA during stressors. Following weight loss, absolute MSNA was significantly lower throughout low-and moderate-intensity handgrip exercise compared with a control group of participants with obesity.…”
Section: Obesitymentioning
confidence: 99%
“…Our previous studies focused on the clinical importance of exercise BP in detecting high BP and the factors that contribute to exercise BP (fitness and fatness) and the influence of exercise BP on cardiovascular risk (high BP and altered cardiovascular structure) in adolescents ( 92 94 ). One of our previous studies first demonstrated that exercise BP might be a useful tool to rule out underlying high BP or “masked hypertension” in adolescence (Specificity: 86.9%, NPV: 95.5%) ( 92 ).…”
Section: Clinical Relevance Of Abnormal Exercise Bpmentioning
confidence: 99%